Charge sharing modeling in pixel detectors with capacitive charge division. - Marczewski, J. (IEEE Transactions on electron devices)
Pixel detectors with junctions interleaved to readout nodes have been modeled as an electrical network. Time domain analysis of a signal induced by an ionizing particle has been performed. Results are reported, together with a comparison to experimental data.